Technical assistance to CIS countries - Roman Mogilevsky; Aziz Atamanov (Center for Social and Economic Research (CASE), 2008)
During the last two decades the CIS countries have received very significant amounts of technical assistance from international development organizations and bilateral donors. While this has played a positive and important role in the transformation of these societies, practically all stakeholders currently share the opinion that many problems have accumulated in the area of technical cooperation with CIS countries. This paper intends to outline these problems, analyze their underlying reasons - including the changing environment for technical cooperation in the CIS - and the interaction of the interests of beneficiaries, donors and providers in the process of implementing technical cooperation projects. The analysis suggests that a good understanding, recognition and coordination of the interests of all TC stakeholders and a reduction in the information gap between the various participants in the technical cooperation process are necessary for improving the effectiveness of technical cooperation.
Keywords: F35; O19; O21; P33; 330; technical assistance; technical cooperation; TC effectiveness; CIS; Technische Zusammenarbeit; Forschungskooperation; GUS-Staaten